1975
DOI: 10.1159/000279991
|View full text |Cite
|
Sign up to set email alerts
|

New Features in the Pathogenesis of Renal Tuberculosis and Their Significance for its Detection

Abstract: The study of 1,464 cases of renal tuberculosis in 1946–1971 shows that the incidence of this illness has not diminished. The percentage of aged patients and of women has increased. The frequency of previous tuberculosis has decreased and the interval between tuberculosis and renal tuberculosis has increased. These new features show that the role of general pathogenic factors regresses whereas that of local factors progresses. Among the latter, the main factor is a disturbance of the urine outflow from the kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In fact, in a later publication that was more detailed and had a larger sample size [12] , Shabad evaluated 1464 cases of renal tuberculosis in the two largest hospitals in Moscow between 1946 and 1971. In this study, the following were observed over the years: Higher incidence of renal tuberculosis in female patients, with a predominance of cases in women (63.4 %) in the last decade; In 71 % of the cases, there was a lesion in the upper pole, and in 61 %, there was an intrarenal pelvis, which was associated with a greater chance of obstruction; In 15 % of the cases, there was a history of previous kidney disease, such as malformation, nonspecific chronic pyelonephritis, kidney stones and kidney trauma; In patients with unilateral renal malformation, tuberculosis occurred in the malformed kidney at a frequency five times higher than in the normal contralateral kidney; Women with previous pregnancies had a higher frequency of tuberculosis in the right kidney than the left kidney (ratio 1.5:1); and In 30 % of women, the onset of renal tuberculosis occurred in connection with pathological pregnancies and deliveries and gynecological diseases or surgeries; …”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a later publication that was more detailed and had a larger sample size [12] , Shabad evaluated 1464 cases of renal tuberculosis in the two largest hospitals in Moscow between 1946 and 1971. In this study, the following were observed over the years: Higher incidence of renal tuberculosis in female patients, with a predominance of cases in women (63.4 %) in the last decade; In 71 % of the cases, there was a lesion in the upper pole, and in 61 %, there was an intrarenal pelvis, which was associated with a greater chance of obstruction; In 15 % of the cases, there was a history of previous kidney disease, such as malformation, nonspecific chronic pyelonephritis, kidney stones and kidney trauma; In patients with unilateral renal malformation, tuberculosis occurred in the malformed kidney at a frequency five times higher than in the normal contralateral kidney; Women with previous pregnancies had a higher frequency of tuberculosis in the right kidney than the left kidney (ratio 1.5:1); and In 30 % of women, the onset of renal tuberculosis occurred in connection with pathological pregnancies and deliveries and gynecological diseases or surgeries; …”
Section: Discussionmentioning
confidence: 99%